Harmonization of Postgraduate Training System with the Certification of Candidates of Sciences - S. I. Pakhomov; V. A. Gurtov; L. V. Shchegoleva (Высшее образование в России)
Harmonization of Postgraduate Training System with the Certification of Candidates of Sciences The activities of the postgraduate school and the network of dissertation councils represent the stages of the trajectory of the formation of a researcher with an academic degree. This means that their activities should be coordinated. The article discusses several approaches to the harmonization: at the level of each organization – by the presence or absence of one of the participants in the trajectory, and at the thematic level. For each approach, statistical estimates of consistency are calculated, and cartographic representations of indicators in the context of the subjects of the federation are given. The analysis showed that, in general, there is a territorial alignment of the organizations for postgraduate student training with the organizations in which a candidate’s thesis can be defended.